Wireless power transfer for Battery Management System in Electric Vehicle Applications (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Wireless power transfer (WPT) using magnetic resonance is the technology which could set human free from than annoying wires. In fact, the WPT adopts the same basic theory which has already been developed for at least 30 years with the term inductive power transfer (IPT). WPT technology is developing rapidly in recent years. At kilowatts power level, the transfer distance increases from several millimeters to several hundred millimeters with a grid to load efficiency above 90%.        The advances make the WPT very attractive to the electric vehicle(EV) charging applications in both stationary and dynamic charging scenarios. This paper reviewed the technologies in the WPT area applicable to EV wireless charging. By introducing WPT in EVs, the obstacles of charging time, range and cost can be easily mitigated. Battery technology is no longer relevant in the mass market penetration of EVs. It is hoped that researcher could be encouraged by the state-of-the-art achievements, and push forward the further development of WPT as well as the expansion of EV.